The Impact of Business Models on the Internationalization of Enterprises as a New Area of Research - Bołoz , Rafał (Studia Oeconomica Posnaniensia, 2018)
The aim of the paper is to identify the relationship between the paradigm of business models and the theory of internationalization - in a theoretical dimension. The paper presents research approaches that are common for both dimensions. In the context of the presented perspectives, the areas where theories show complementarity and interact with each other are emphasized.